Effect of local application of bone morphogenetic protein -2 on experimental tooth movement and biological remodeling in rats - Wang, Menglin; Fan, Jiadong; Wang, Aoao; Jin, Xiang; Zhang, Zhenbao; Hu, Xiantong; Liu, Le; Zhao, Yantao; Li, Yanfeng (Frontiers in Physiology, 2023)
Background: This study attempts to detect the potential effects of local bone morphogenetic protein -2 (BMP-2) on orthodontic tooth movement and periodontal tissue remodeling. Methods: Forty adult SD rats were randomly divided into four groups: blank control group, unilateral injection of BMP-2 on the pressure side or tension side of orthodontic teeth and bilateral injection of BMP-2. Their maxillary first molar was moved by a 30g constant force closed coil spring. 60μl of BMP-2 with a concentration of 0.5μg/ml was injected into each part at a time. In addition, three rats were selected as healthy control rats without any intervention. Fluorescent labeled BMP-2 was used to observe the distribution of exogenous BMP-2 in tissues. Micro-CT was used to measure the microscopic parameters of tooth displacement, trabecular bone and root absorption volume. Three different histological methods were used to observe the changes of tissue remodeling, and then the number of osteoclasts and the content of collagen fibers were calculated. Results: Compared with the blank control group, BMP-2 injection reduced the movement distance and increased the collagen fiber content and bone mass (p<0.01). There was no significant difference in tooth movement distance, BV/TV ratio and BMD between injection sites in unilateral injection group (p>0.05). In the case of bilateral injection of BMP-2, the osteogenesis is enhanced. Unilateral injection of BMP-2 did not promote root resorption, but double injection showed root resorption (p<0.01). Conclusion: Our study does show that the osteogenesis of BMP-2 is dose-dependent rather than site-dependent when a certain amount of BMP-2 is applied around orthodontic teeth. Local application of BMP-2 around orthodontic teeth in an appropriate way can enhance bone mass and tooth anchorage without increasing the risk of root absorption volume. However, high levels of BMP-2 may cause aggressive root resorption. These findings are of great significance, that is, BMP-2 is an effective target for regulating orthodontic tooth movement.